Circumstances of Human–Bat interactions and risk of lyssavirus transmission in metropolitan France. (8th August 2020) - Parize, Perrine; Travecedo Robledo, Isabel Cristina; Cervantes‐Gonzalez, Minerva; Kergoat, Lauriane; Larrous, Florence; Serra‐Cobo, Jordi; Dacheux, Laurent; Bourhy, Hervé
Abstract: Since the elimination of dog and terrestrial wild animal rabies, bat exposures remain the only source of autochthonous lyssavirus transmission to humans in Western Europe. European bats have already been found infected with several lyssaviruses, and human–bat interactions represent a risk of viral transmission and fatal encephalitis for humans. In this study, we aim to better characterize exposures to bats in metropolitan France from 2003 to 2016 and to identify circumstances associated with exposures to lyssavirus‐positive bats. Two complementary sources of data were analysed: 1/ data associated with bats responsible for human exposure received for Lyssavirus testing by the French National Reference Centre for Rabies (NRCR); and 2/ data pertaining to individuals seeking medical care through the French Anti‐Rabies Clinics network after contact with a bat. From 2003 to 2016, 425 bats originating from metropolitan France were submitted to the NRCR and 16 (4%) were found positive with a lyssavirus (EBLV‐1b was diagnosed in 9 bats, EBLV‐1a in 6 and BBLV in one specimen). The two factors associated with bat positivity in our study were the female sex and the bat belonging to the E. serotinus species. During the same study period, 1718 individuals sought care at an Anti‐Rabies Clinic after exposure to a bat resulting in an estimated incidence of human–bat interactions of 1.96 per 10 6 person‐years. The two most frequent circumstances of exposure were handling or bites. Interactions mostly involved one adult human being and one live and non‐sick‐looking bat. Our study provides new insights about circumstances of human–bat interactions and may be helpful to target prevention interventions to improve the awareness of the population of the risk of lyssavirus transmission.